Learning Outcomes Generated through the Collaborative Processing of Expert Peer Feedback - Nicholas Carr; Paul Wicking (National Research University Higher School of Economics, 2022)
Background. Studies have shown that the collaborative processing of feedback on a jointly produced text facilitates language learning in a traditional classroom. However, it is still unknown whether there are similar learning benefits when the feedback is provided through an online modality from an expert peer during an international virtual exchange (IVE). Purpose. The present study fills this gap in the literature by investigating Japanese learners engaged in processing written corrective feedback from expert language users in the United States. Methods. Qualitative data concerning students' perceptions of learning outcomes were collected via retrospective interviews and narrative frames, then triangulated with their first and final drafts of written texts and analyzed using activity theory (AT). Results. Findings indicate that learning benefits accrued in areas of language skills such as vocabulary, spelling, and grammar, as well as deepening learners' reflexive awareness of themselves as language users. Conclusion. A discussion of these findings, informed by sociocultural theory and shaped by the categories of AT, brings to light some of the interactional dynamics that contributed to the creation of these outcomes. These interactional dynamics show that the learning benefits of the activity primarily resided in the peer-to-peer interactions rather than interactions with the expert-peer.